2012
DOI: 10.1371/journal.pone.0039333
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Pyrosequencing Reveals Bacterial Dysbiosis in the Duodenum of Dogs with Idiopathic Inflammatory Bowel Disease

Abstract: BackgroundCanine idiopathic inflammatory bowel disease (IBD) is believed to be caused by a complex interaction of genetic, immunologic, and microbial factors. While mucosa-associated bacteria have been implicated in the pathogenesis of canine IBD, detailed studies investigating the enteric microbiota using deep sequencing techniques are lacking. The objective of this study was to evaluate mucosa-adherent microbiota in the duodenum of dogs with spontaneous idiopathic IBD using 16 S rRNA gene pyrosequencing.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
206
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 201 publications
(228 citation statements)
references
References 36 publications
13
206
4
5
Order By: Relevance
“…As in humans, an interplay between the intestinal microbiota together with an underlying genetic susceptibility of the host and dietary and environmental factors, are implicated in the development of disease [7,32]. While recent studies have reported a dysbiosis in duodenal samples of dogs with IBD, limited data are available describing the fecal microbiota in these dogs [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in humans, an interplay between the intestinal microbiota together with an underlying genetic susceptibility of the host and dietary and environmental factors, are implicated in the development of disease [7,32]. While recent studies have reported a dysbiosis in duodenal samples of dogs with IBD, limited data are available describing the fecal microbiota in these dogs [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Chimeras were excluded using the software B2C2 (http://www. researchandtesting.com/B2C2.html) [7,19]. Operational taxonomic units (OTUs) were defined as sequences with at least 97% similarity using QIIME.…”
Section: -Pyrosequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…5,17,20,38,55,88,89,115,117,119,126 These microbial changes are accompanied by underlying susceptibilities in the innate immune system of dogs and cats with chronic enteropathies, such as idiopathic IBD, further demonstrating the relationship between gut microbiota and host health. 55,62,63,78,86 It is been shown that the canine microbiota changes with diarrhea, with the most profound changes in dogs with acute hemorrhagic diarrhea (AHD), 117 and characterized by significant decreases in Blautia, Ruminococcaceae including Faecalibacterium, and Turicibacter spp., and significant increases in genus Sutterella and Clostridium perfringens compared to healthy dogs (Fig.…”
Section: The Microbiome In Gastrointestinal Diseasesmentioning
confidence: 99%
“…94 In dogs with IBD, the mucosa-adherent microbiota of the small intestine is primarily comprised of Proteobacteria, especially E. coli-like organisms 126 or Pseudomonas, 119 with lower proportions of Firmicutes and Bacteroidetes compared to healthy dogs. 115 Boxer dogs and French Bulldogs with granulomatous colitis also have dysbiosis of their intestinal microbiome. Microbiota analysis based on sequencing of 16 S rRNA genes in combination with FISH has revealed invasive E. coli bacteria present in multifocal clusters within macrophages in the colonic mucosa.…”
Section: The Microbiome In Gastrointestinal Diseasesmentioning
confidence: 99%